Dampak Perceraian Orangtua terhadap Pembentukan Kepribadian Santri: Studi di Dayah Liqaurrahmah, Tungkop - Ichsan Hafizh; Suarni Abdullah; Boihaqi bin Adnan (Yayasan Cendekia Gagayunan Indonesia, 2025)
This study aims to analyze the factors that cause parental divorce from students in Dayah Liqaurrahmah, Tungkop, and examine the negative impact of divorce on the academic, social, and emotional development of students. The background of this research departs from the increasing number of divorce cases in society that also affect the lives of children, including those who study in Islamic boarding schools. The research method used is descriptive qualitative with a sociological-empirical approach. The data was collected through in-depth interviews with three students of Dayah Liqaurrahmah, Tungkop, whose parents have divorced. The analysis was carried out thematically to identify the social and emotional patterns that arise after parental separation. The results of the study show that the main factors causing divorce include protracted domestic conflicts, imbalances in roles and responsibilities, differences in life principles, and weak communication between couples. This condition has a significant impact on children, especially in the form of decreased motivation to learn, changes in social behavior, feelings of loss of emotional support, and tension in family relationships. Parental divorce has a complex negative influence on the psychosocial welfare of students. In addition, there is a need for psychological assistance and continuous counseling in the pesantren environment, increasing the role of supervisors in detecting changes in student behavior, and cooperation between dayah and families to create a stronger emotional support system for children who are victims of divorce.